PINDAR, ISTHMIAN 4.47. (December 2020) - Lane, Nicholas
Abstract : 45 τόλμᾳ γὰρ εἰκώϲ θυμὸν ἐριβρεμετᾶν θηρῶν λεόντων ἐν πόνῳ, μῆτιν δ᾽ ἀλώπηξ, αἰετοῦ ἅ τ᾽ ἀναπιτναμένα ῥόμβον ἴϲχει· χρὴ δὲ πᾶν ἔρδοντ᾽ ἀμαυρῶϲαι τὸν ἐχθρόν. 46 θηρᾶν: Heyne For he [ sc . Melissus, the victor] resembles the boldness of loudly roaring wild lions in his heart during the struggle, but in skill he is a fox, which rolls on its back to check the eagle's swoop. One must do everything to diminish one's opponent.